Management Control in Cameroon Municipal Areas: A Response to the Urgent Issue of Risk Management - LEA, Isaac; MAYEGLE , François-Xavier (Archives of Business Research, 2021)
Abstract Generally, Cameroon municipalies encounter organisaonal risks. This research has idened a typology of such risks and presents management control as a cursor of enlightenment and governance in controlled risk. This objecve is achieved aer using a quantave method through a hypotheco-deducve approach aimed at tesng three hypotheses; the study was conducted using a quesonnaire administered in 9 out of 10 regions in Cameroon. At the end, this study highlights that management control in Cameroon municipal areas is void of proacve tools, and uses only tradional tools. It also highlights that ways of implemenng management control in Cameroon municipalies are not conducive to reduce risks. Key words: control management, organisaonal risks, municipality.